Electron Beam-Treated Enzymatically Mineralized Gelatin Hydrogels for Bone Tissue Engineering - Riedel, Stefanie; Ward, Daniel; Kudláčková, Radmila; Mazur, Karolina; Bačáková, Lucie; Kerns, Jemma G; Allinson, Sarah L; Ashton, Lorna; Koniezcny, Robert; Mayr, Stefan G; Douglas, Timothy E L (Journal of functional biomaterials, 2021)
Biological hydrogels are highly promising materials for bone tissue engineering (BTE) due to their high biocompatibility and biomimetic characteristics. However, for advanced and customized BTE, precise tools for material stabilization and tuning material properties are desired while optimal mineralisation must be ensured. Therefore, reagent-free crosslinking techniques such as high energy electron beam treatment promise effective material modifications without formation of cytotoxic by-products. In the case of the hydrogel gelatin, electron beam crosslinking further induces thermal stability enabling biomedical application at physiological temperatures. In the case of enzymatic mineralisation, induced by Alkaline Phosphatase (ALP) and mediated by Calcium Glycerophosphate (CaGP), it is necessary to investigate if electron beam treatment before mineralisation has an influence on the enzymatic activity and thus affects the mineralisation process. The presented study investigates electron beam-treated gelatin hydrogels with previously incorporated ALP and successive mineralisation via incubation in a medium containing CaGP. It could be shown that electron beam treatment optimally maintains enzymatic activity of ALP which allows mineralisation. Furthermore, the precise tuning of material properties such as increasing compressive modulus is possible. This study characterizes the mineralised hydrogels in terms of mineral formation and demonstrates the formation of CaP in dependence of ALP concentration and electron dose. Furthermore, investigations of uniaxial compression stability indicate increased compression moduli for mineralised electron beam-treated gelatin hydrogels. In summary, electron beam-treated mineralized gelatin hydrogels reveal good cytocompatibility for MG-63 osteoblast like cells indicating a high potential for BTE applications.
Keywords: bone tissue engineering; electron beam treatment; enzymatic mineralisation; gelatin hydrogels